De-Escalating Impact of Student Support Impediments in Turbulent Environment By Integrating Technology Inclination Within Open Distance and E-Learning Context - NGWENYA, Charles Tony Simphiwe; MDLALOSE, Nonhle Lydia; ZUNGU, Knowledge Lungisani (International Journal of Environmental, Sustainability, and Social Science, 2024)
This study undertakes the explanatory of a transition from a conventional teaching and learning mode delivery into an Open Distance and e-Learning blended delivery method. The researchers analyses the constraints and hindrances that catapult the sustainable implementation of this existential and contemporary transition. The fundamental objective is predicated seamless transition that integrate requisite digital and technology oriented leaner resources and capabilities from a socio-economic perspective. A positivist paradigmatic stance and philosophy within quantitative inquiry methodology, guided by the positivist philosophical framework, was undertaken and research instrument based on descriptive examination was answered by approximately 212. The findings indicates a diverse degree of insights in terms of student characterisation on the current transition by illuminating inequalities amongst students' in digital resources and online infrastructure access. The implication in the inquiry reiterate the bespoke prioritization by the pedagogical decision makers of digital resources and a conducive environment for the leaner experience and success in reaching their dreams. Second, the inquiry illuminate the significant prioritization of the social capital inequalities that characteristics that the students within the higher learning community of practice. Future related studies to investigate he intangible constraints such as student’s behaviours, intentions, motivations and orientations’ in a transitory era.